Right renal vein elongation with the inferior vena cava for cadaveric kidney transplants: an old neglected surgical approach - Baptista-Silva, José Carlos Costa [UNIFESP] (2005)
INTRODUCTION: Short right renal vein is a frequent and well-known technical inconvenience that is commonly observed during transplantation of the right kidney. We present our experience with the elongation of short cadaveric right renal veins using the contiguous vena cava during cadaveric renal transplants. METHODS: We performed 34 kidney transplantations with a short right renal vein requiring elongation using the inferior vena cava, to make the venous anastomosis technically feasible. The elongated right renal vein was anastomosed end to side to the external iliac vein in 24 patients, to the common iliac vein in 8 patients and to the inferior vena cava in 2 patients. The right renal artery with an aortic patch was implanted end to side in 33 patients, and end to end without aortic patch to the internal iliac artery in one patient. RESULTS: In all cases, the vascular anastomoses were easily performed in the recipient and no thrombosis was observed. CONCLUSION: Elongation of a short right renal vein with the inferior vena cava is a feasible mean to overcome technical problems that may compromise the results of cadaveric renal transplantation.